TEAMWORK AND EMPLOYEE JOB SATISFACTION IN BENUE INVESTMENT AND PROPERTY COMPANY, MAKURDI, BENUE STATE - TOR NORA (International Studies Journal)
The aim of the study was to examine the relationship between teamwork and employee satisfaction in Benue Investment and Property Company, Makurdi. Specific objectives were to: ascertain if team trust, verify if esprit de Corp and team communication with employee satisfaction in Benue Investment and Property Company, Makurdi, Benue State. The study adopted survey research design. The population of the study was 118, census sampling technique was used to retain the whole population as sample size. The study found that Team trust, espirit de Corp and team Communication have significant effect on employee satisfaction in Benue Investment and Property Company, Makurdi, Benue State. Based on the results the study concludes that, the independent variables of teamwork (team trust, espirit de corp, and team communication) are predictors of employee satisfaction (employee engagement, employee retention and employee feedback) in Benue Investment and Property Company, Makurdi, Benue State. The study recommended that, BIPC management should promote team trust among organization members which will thereafter enable an individual to put more of his/her resources into tasks that will bring about organizational performance. Teamwork should be seen as an effective operational strategy and adopted not as an ad hoc strategy but one that should be sustained, BIPC should promote espirit de corp in designing tasks and activities based on team to get better and desired results, teamwork activity within the organization is very much beneficial and its effect is directly on employee performance. When an employee acquires adequate opportunities of teamwork his/her performance automatically improves and he/she will be satisfied with the job, and BIPC should promote team communication among team members in the organizations. This is because anything accomplished by humans involves communication and inadequate communications between people may lead to the poor achievement of goals.